HUBUNGAN KUALITAS TIDUR DAN KONSUMSI GARAM DENGAN TINGKAT HIPERTENSI DI DESA KUTA TUALAH TAHUN 2024 - Sembiring Tella Maris; Simatupang Lusia Lenny (PT. Hasba Edukasi Mandiri, 2026)
Hypertension is a condition characterized by increased arterial blood pressure and remains a major global health problem. According to the World Health Organization (WHO) in 2015, approximately 1.13 billion people worldwide suffered from hypertension, and the number is projected to rise to 1.5 billion by 2025. This study aimed to determine the relationship between sleep quality and salt consumption with hypertension levels in Desa Kuta Tualah. This study used a quantitative method with a cross-sectional design. The population consisted of 30 individuals with hypertension, selected using total sampling. The research instruments included the Pittsburgh Sleep Quality Index (PSQI), Food Frequency Questionnaire (FFQ), and 24-hour food recall. Data were analyzed using the Pearson correlation test. The results showed a significant relationship between sleep quality and hypertension level (p = 0.001) and between salt consumption and hypertension level (p = 0.031) (p < 0.05).